2018
DOI: 10.1002/stab.201810588
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in tubular joints experiments in Brazil

Abstract: Dedicated to Prof. Dr.‐Ing. habil. Joachim Lindner on the occasion of his 80th birthday The aesthetical and structural advantages of tubular structural elements sustained the increase in their use in Brazil in last decades. The joints between tubular members remain a critical issue, with many studies indicating that further research is still needed, particularly for some geometries. In the past, some experiments on the influence of the chord stresses over the brace load capacity were published, but a definitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It should be noted that the Lima et al [4] formulation presented values major to those obtained in the numerical models. Onde again, it is necessary to mention that the parameter used by the authors to validate the equation is not applicable for the studid cases because the thickness doubler plate studied in this paper is not equal to chord one.…”
Section: Comparison With the Structural Formulationmentioning
confidence: 68%
See 2 more Smart Citations
“…It should be noted that the Lima et al [4] formulation presented values major to those obtained in the numerical models. Onde again, it is necessary to mention that the parameter used by the authors to validate the equation is not applicable for the studid cases because the thickness doubler plate studied in this paper is not equal to chord one.…”
Section: Comparison With the Structural Formulationmentioning
confidence: 68%
“…The second study [5] is directed related to the influence of the thickness doubler plate on the T-joint's structural behaviour, differently from the first one. The following equations presented the two proposals developed by Lima et al [4] and Souza [5], respectively.…”
Section: Design Prescription For the Reinforced T-jointmentioning
confidence: 99%
See 1 more Smart Citation
“…A further experimental investigation will be performed in the laboratory to better understand the austenitic stainless steel tubular T-joints subjected to chord axial forces. For carbon steel, some experimental evidence from previous research conducted by the authors of the present paper has shown that the design rules for T-joints with chord axial effects are not adequate and need to be modified [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other recent studies (Kim and Lee, 2020; Lima et al, 2018a; Nizer et al, 2016) have shown that, depending on the intensity of tension stresses in a chord, an increase in joint resistance could occur, what was never found in compression cases. For cases with compression stresses, the brace-to-chord ratio was identified as a critical parameter that influenced the joint strength of T-joints with reinforcements (Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 91%